Ki-67 and Bcl-2 in colorectal polyps with breast cancer - Ibrahim Gelincik (Wolters Kluwer Medknow Publications, 2011)
Background: The most common second primary cancer in women who survive breast cancer is colorectal cancer. Population cohort studies suggest that the risk of colorectal cancer is also high in female relatives of women with breast cancer compared to the general population. The histological distinction between a large hyperplastic polyp and a serrated adenoma is not straightforward and there is probably no sharp division between hyperplastic polyposis and 'serrated adenomatous polyposis'. Aim: The aim of the study was to define the distribution of Ki-67 and Bcl-2 protein in hyperplastic colorectal polyps of women with breast cancer. Materials and Methods: A cross-sectional, controlled study was conducted in 40 women with and without breast cancer who had hyperplastic colorectal polyps. The patients were divided into two groups: Group A (a control group of women without breast cancer, n = 20) and Group B (a study group of women with breast cancer, n = 20). The expression of Ki-67 and Bcl-2 protein was assessed on the basis of quantity of immunostaining, by counting antigen positive cells, in comparison with normal mucosa. Student's t-test and the chi-square test were used to analyse Ki-67 and Bcl-2 expression, respectively. Results: Statistical significance was established at P < 0.05. The mean percentage of Ki-67 stained nuclei in Groups A and B was 25.11 ± 2.07 and 41.51 ± 1.86, respectively (P < 0.003), whereas the percentage of cases with cells expressing Bcl-2 in Groups A and B was 15% and 85%, respectively (P < 0.002). Conclusions: In the present study, greater proliferative activity and greater expression of the antiapoptotic protein Bcl-2 was found in the hyperplastic colorectal polyps of women with breast cancer.